Transfection of Escherichia coli Spheroplasts I. General Facilitation of Double-Stranded Deoxyribonucleic Acid Infectivity by Protamine Sulfate - Benzinger, Rolf (1971)
The addition of 25 μg of protamine sulfate per ml to lysozyme-ethylenediamine-tetraacetic acid spheroplasts of Escherichia coli stimulates transfection not only for T1 phage deoxyribonucleic acid (DNA; Hotz and Mauser, 1969) but also for the following phage DNA species: lambda, 10,000-fold to an efficiency of 10(−3) infective centers per DNA molecule; φX174 replicative form, 300-fold to an efficiency of 5 × 10(−2); fd replicative form, 300-fold to 10(−6); T7, 300-fold to 3 × 10(−7). Three native phage DNA species were not infective at all in the absence of protamine sulfate but were infective in the presence of protamine sulfate with the following efficiencies: T4, 10(−5); T5, 3 × 10(−6); and P22, 3 × 10(−9). The effect of protamine sulfate is specific for double-stranded DNA. The application of infectivity assays to the study of phage DNA replication, recombination, prophage integration, prophage excision, and interspecies transfection are discussed.